OPTIMIZATION OF PROCESS PARAMETERS OF FENIMOCOCRTI HIGH ENTROPY ALLOY COATING ON 45# STEEL SURFACE - ZHANG Qi; LI ZhongWen; YU ZhiShui (Jixie qiangdu)
For achieving high hardness and high performance alloy coating,the high entropy coating of FeNiMoCoCrTi was prepared by laser cladding on the surface of 45# steel. The process parameters were optimized by using the orthogonal test method,for getting the best combination of process parameters,the measured data were sorted out and summarized by a combination of Mathematical Polarity and Variance analysis method,XRD phase analysis and hardness test were carried out. The results show that the main factors that affect the hardness and performance of the coating are the laser power and scanning speed,and the defocusing amount mainly affects the hardness. The preferred combination of process parameters is laser power 3000 W,scanning speed 0. 015 m/s,defocusing amount 50 mm. The main phase composition of the coating is FCC + BCC + Simple cubic1+ Simple cubic2+ Simple cubic3+ Laves phase.